Viabilitas Sel Bakteri Dengan Cryoprotectant Agents Berbeda (Sebagai Acuan Dalam Preservasi Culture Collection di Laboratorium Mikrobiologi) - Lela Susilawati; Ethik Susiawati Purnomo (Biogenesis: Jurnal Ilmiah Biologi, 2016)
The aim of this research was to determine the viability of bacterial cells on different cryoprotectant agents. Three kind of cryoprotectant agents and two types of mixed cryprotectant were applied to evaluate the ability of bacteria to growth on Agar medium. Four isolates were used namely Escherichia coli ATCC 35218, Staphylococcus aureus ATCC 25923, Shigella flexneri ATCC 12022 and Bacillus subtilis ATCC 6051. All strains were preserved in 10% skimmed milk, 10% glycerol, 10% DMSO, 10% glycerol:10% skimmed milk and 10% DMSO:10% skimmed milk at -80°C for sixty days. Immediately after preserved, the bacteria were tested their viability at day 30 and 60 during storage. The enumeration of samples taken from cultures in NA media. Better survival of bacterial cells after freezing was shown in all tested cryprotectant agents. Highest microbial viability was shown in 10% skimmed milk, 10% glycerol and mixed 10%DMSO:10% skimmed milk. Hence, those three types of cryoprotectant agents can be recommended to preserve bacterial cell for long term storage.